Theoretical studies on leaky-SAW properties influenced by layers on anisotropic piezoelectric crystals - Wallner, Paul; Ruile, Werner; Weigel, Robert (IEEE Transactions on Ultrasonics Ferroelectrics and Frequency Control, 2000)
Theoretical studies on the behavior of leaky-SAW (LSAW) properties in layered structures were performed. For these calculations rotYX LiTaO 3 and rotYX LiNbO3 LSAW crystal cuts were used, assuming different layer materials. For LSAWs both the velocity and the inherent loss due to bulk wave emission into the substrate are strongly influenced by distinct layer parameters. As a result, these layer properties like elastic constants or thickness have shown a strong influence on the crystal cut angle of minimum LSAW loss. Moreover, for soft and stiff layer materials, a different shift of the LSAW loss minimum can occur. Therefore, using double-layer structures, the shift of the LSAW loss minimum can be influenced by appropriate chosen layers and ratios
elib2cris::1512001600,wallner2000
Keywords: SAW; Crystal